Strategies of Islamic Boarding Schools Toward Moral Changes in the Millennial Generation - Robi Gunawan; Darmaji Darmaji; Reni Elisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
In today's digital era, particularly as a result of the COVID-19 pandemic, the millennial generation is experiencing a crisis of uswah hasanah (exemplary role models). After nearly three years of being accustomed to online learning, students' morals and habits have gradually shifted away from religious norms. This situation is further exacerbated by the ease of access to vulgar images and videos that deviate from Islamic teachings, worsening the future outlook of young people's religious values. When formal education fails to offer a solution for parents facing this reality, Islamic boarding schools (pesantren) present an educational model that prioritizes moral development through the salafiyah system, where the kyai (Islamic scholar) serves as the central figure and role model, and the pesantren environment becomes the place to internalize and apply knowledge. Through this 24-hour learning method, millennial students—known as santri—receive constant supervision and guidance from the kyai, both physically (dzahir) and spiritually (batin), with the aim of shaping them into well-rounded individuals (insan kamil). Based on this reality, the author conducted a study to examine how significantly the presence of pesantren influences the morality of the millennial generation in its surrounding environment using descriptive and verifiable methods. This is exemplified by KH. Nurhusen Hidayatulloh, leader of Pesantren Darul Muta’alimin 06 Sumber Agung, in how he educates his students. Located in the village of Sumber Agung, Way Sulan District, South Lampung Regency—a community largely composed of informal laborers with low levels of education and limited religious understanding—teenagers often lack proper religious guidance from their parents. However, significant changes have been observed: community interest in religious gatherings and dhikr has increased, and youth are becoming more actively involved in various religious activities.